2004
DOI: 10.1002/cne.20181
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hippocampal cholinergic innervation is unrelated to recognition memory impairment in aged rhesus monkeys

Abstract: Alterations in the basal forebrain cholinergic system have been widely studied in brain aging and Alzheimer's disease, but the magnitude of decline and relationship to cognitive impairment are still a matter of debate. The rhesus monkey (Macaca mulatta) provides a compelling model to study age-related memory decline, as the pattern of impairment closely parallels that observed in humans. Here, we used antibodies against the vesicular acetylcholine transporter and a new stereological technique to estimate total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…During normal aging, the volume of the hippocampus (total or any of its subfields) remains stable in rhesus monkeys (Peters et al 1996;Calhoun et al 2004;Shamy et al 2006Shamy et al , 2010Makris et al 2010). This is in contrast to a substantial number of MRI studies reporting a reliable age-related decline in hippocampal volume in healthy humans (Kaye et al 1997;Mueller et al 1998;Tisserand et al 2000;Raz et al 2004;Walhovd et al 2009).…”
Section: Gross Anatomy Of Hippocampal and Related Cortical Regionsmentioning
confidence: 89%
See 2 more Smart Citations
“…During normal aging, the volume of the hippocampus (total or any of its subfields) remains stable in rhesus monkeys (Peters et al 1996;Calhoun et al 2004;Shamy et al 2006Shamy et al , 2010Makris et al 2010). This is in contrast to a substantial number of MRI studies reporting a reliable age-related decline in hippocampal volume in healthy humans (Kaye et al 1997;Mueller et al 1998;Tisserand et al 2000;Raz et al 2004;Walhovd et al 2009).…”
Section: Gross Anatomy Of Hippocampal and Related Cortical Regionsmentioning
confidence: 89%
“…In the DG, CA2/3, and CA1, the length of cholinergic fibers decreases with age, but this age-related decline does not correlate with recognition memory deficits as measured by DNMS scores (Calhoun et al 2004). Despite converging evidence for age-dependent vulnerability of the cholinergic system, the decline in hippocampal cholinergic innervation is not sufficient to account for DNMS impairment (Calhoun et al 2004). Thus, the functional and cognitive consequences of these morphological changes remain to be defined.…”
Section: Acetylcholinementioning
confidence: 97%
See 1 more Smart Citation
“…A higher density of acetyl cholinesterase has been reported in the rostral hippocampus (Rosene and Van Hoesen, 1987). Additionally, when considering the extent to which cholinergic fiber density and loss are evident in hippocampal subfields, a study based on non-human primates reported that there is a higher density in CA3 as compared to dentate gyrus and CA1, though loss of cholinergic innervation in aging is consistent across the longitudinal axis of the hippocampus (Calhoun et al, 2004). CA1 and CA3 have been found to lie primarily within the hippocampal head, and the dentate gyrus primarily within the hippocampal body in humans (Malykhin et al, 2010), which together with the aforementioned data further suggest there is increased cholinergic activity within the head of the hippocampus as compared to the body and tail, and loss of these fibers in AD may contribute to a decline in memory.…”
Section: Discussionmentioning
confidence: 99%
“…Axon length was assessed using the SpaceBalls probe under Koehler illumination at 63x (Zeiss PlanAchromat, N.A. 1.4) (Calhoun and Mouton, 2000;Mouton et al, 2002;Calhoun et al, 2004;Kreczmanski et al, 2005). SpaceBalls is a stereological tool that places sampling hemispheres for lineal features in the context of a fractionator sampling scheme (Mouton, 2002).…”
Section: Axon Length Densitymentioning
confidence: 99%